Linguistic Landscapes In Desa Kuta - Mulyawan, I Wayan; Ratna Erawawti, Ni Ketut (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-July, 2019)
This research aimed to identify the presence of Linguistic Landscapes (LL) in Desa Kuta . LL is sociolinguistic study of language used in outdoor signage that firstly introduce by Landry and Bourhis (1997). Desa Kuta as one of tourist destination in Bali experiences a great development due to globalization effect. This great development can be seen clearly through the presence of outdoor signs along the main roads of Desa Kuta . The research was conducted from February to March 2019. The finding showed there are 2.549 signs along the main roads of Desa Kuta . The language used mostly in English with 1.332 signs (52%). As for the types, there are 1.603 signs of commercial signs (65%). In term of the function, 2.320 signs (93%) are informative.